Modern EPR spectroscopy fundaments and methods (EMagRes Bks, 2018)
"Provides an introduction to those needing to use infrared spectroscopy for the first time, explaining the fundamental aspects of this technique, how to obtain a spectrum and how to analyse infrared data covering a wide range of applications. Includes instrumental and sampling techniques. Covers biological and industrial applications. Includes suitable questions and problems in each chapter to assist in the analysis and interpretation of representative infrared spectra."--